Geomorphology - Gutierrez, Mateo (CRC Press/Balkema, 2013)
"This primary text provides students with a basic understanding of the origin of landforms and the processes that shape them by discussing the elementary concepts that can be identified, mapped and interpreted of the various forms that constitute the earth's surface. It teaches students to make an assessment of the influence of external geologic processes on human activity and helps to understand landform history and dynamics, and predicting future changes in morphology of the Earth, its organization and its typology guided by different bioclimatic conditions"--Provided by publisher.